PENGARUH APLIKASI MARBEL MEMBACA TERHADAP KEMAMPUAN MEMBACA PERMULAAN PADA SISWA KELAS I SDN GANDASARI 3 KOTA TANGERANG - Nirmala Septia; Sumiyani; Yenni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Early reading ability is a crucial foundation for first grade students as they move forward in their learning journey. In today’s fast-growing digital world, many educational applications are designed to make learning more attractive and interactive, one of which is Marbel Membaca. This study aimed to investigate how effectively the application supports the improvement of students’ early reading skills. The research was carried out at SDN Gandasari 3, Tangerang City, using a quantitative approach with a One-Group Pretest-Posttest Design. The participants consisted of 31 first grade students. Data were collected through reading performance tests, interviews, and documentation, and further analyzed with SPSS version 25. The findings revealed a significance value of 0.000 < 0.05, confirming a strong influence of the treatment. Beyond statistical significance, the contribution of Marbel Membaca reached 89.4% in improving students’ early reading ability. This result highlights that digital learning applications are more than supplementary tools; they can be effective strategies to cultivate interest, strengthen literacy foundations, and encourage reading habits from an early stage of education